2019
DOI: 10.1002/pbc.27957
|View full text |Cite
|
Sign up to set email alerts
|

Eutectic mixture of lidocaine and prilocaine versus 1% lidocaine injection for lumbar punctures in pediatric oncology patients

Abstract: Background:The role of local analgesics for lumbar punctures (LPs) in pediatric oncology patients has not been specifically studied.Aim: To compare the efficacy of eutectic mixture of local anesthetics (EMLA) cream to 1% lidocaine injection for LPs. Method:This was a retrospective observational study of all patients receiving either EMLA cream (EMLA group) or 1% lidocaine subcutaneous injection (lidocaine group) in addition to fentanyl and propofol for LPs over 18 months. Demographics, vital parameters, proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Two reviewers agreed that 6 noninterventional publications met the criteria (Figure). A review of completed pragmatic trials for pediatrics in the ClinicalTrials.gov database from 2017 to 2019 did not identify any clinical trials that reported primarily relying on clinical RWD in the assessment of drug effectiveness. In examining common practices to control for bias in observational studies, we found that half of the 6 publications controlled for confounding by statistical analysis (Table), and none of the publications used propensity score matching.…”
Section: Resultsmentioning
confidence: 99%
“…Two reviewers agreed that 6 noninterventional publications met the criteria (Figure). A review of completed pragmatic trials for pediatrics in the ClinicalTrials.gov database from 2017 to 2019 did not identify any clinical trials that reported primarily relying on clinical RWD in the assessment of drug effectiveness. In examining common practices to control for bias in observational studies, we found that half of the 6 publications controlled for confounding by statistical analysis (Table), and none of the publications used propensity score matching.…”
Section: Resultsmentioning
confidence: 99%
“…This study adds to prior reports demonstrating the safety and efficacy of EMLA cream in pediatric oncology patients undergoing sedation for LP. [9][10][11][12] Our study is notable for its design (prospective, randomized, double blind, and placebo-controlled), relatively large number of events (152), and multiple outcomes assessed (including propofol movement, complications, and satisfaction). Participants randomized to EMLA cream were less likely to move at the time of skin puncture, and were exposed to significantly lower doses of propofol.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Eutectic mixture of lidocaine (2.5%) and prilocaine (2.5%) (EMLA) cream is an Food and Drug Administration-approved local anesthetic indicated for numbing skin before injections and other medical procedures. Several studies have documented the safety and efficacy of EMLA cream for LPs in pediatric oncology patients, [9][10][11] including one which demonstrated that its use allowed for decreased doses of propofol. 12 The study by Whitlow et al 12 was published during our study period and demonstrated less propofol use in a crossover double blind population of 25 patients who each had two procedures.…”
mentioning
confidence: 99%
“…One of the few lidocaine injection-to-EMLA cream comparisons in the literature, a retrospective observational study, reported that EMLA cream shortened LP procedure time, required decreased Propofol, and resulted in fewer adverse events; however, the authors did not examine self-reported pain or nonimmediate outcomes. 9 Assessing self-reported pain is critical when examining pain management strategies as pain is an internal and subjective experience.…”
Section: Introductionmentioning
confidence: 99%